Trends in Eligibility Criteria in Solid Tumor Systemic Therapy Trials Over Time - Jenny Han (Inquiry@Queen's Undergraduate Research Conference Proceedings, 2026)
Background: Cancer clinical trials have used restrictive eligibility criteria, limiting patient access and the generalizability of findings. In response, FRIENDS and ASCO issued recommendations to modernize eligibility criteria in 2017 and 2021. We evaluated whether these recommendations led to measurable changes in eligibility criteria in systemic therapy trials for solid tumours by comparing trial protocols at two points across a 10-year period. Methods: We reviewed randomized clinical trial protocols evaluating systemic therapies for solid tumours published in 2012-2013 and 2022-2023 in the New England Journal of Medicine, The Lancet, and Lancet Oncology. Eligibility criteria aligned with FRIENDS recommendations, including HIV status, brain metastases, and organ dysfunction, were extracted. Descriptive statistics included counts and proportions for categorical variables and means (standard deviation) or medians (interquartile range) for continuous variables. Comparisons used chi-square tests, independent t-tests or Mann-Whitney U tests, as appropriate. Results: We included 42 protocols from 2012–2013 and 98 from 2022–2023, predominantly phase III trials. Recent trials targeted gastrointestinal, genitourinary, and lung cancers (25.5%, 18.4%, and 18.4%), compared to older studies that primarily examined breast, skin, and gastrointestinal cancers (33.3%, 11.9%, and 14.3%). Cancer treatment types have also shifted from a higher proportion of chemotherapy to immunotherapy interventions in more recent trials. Exclusion of patients with brain metastases decreased from 71.4% (2012-13) to 33% (2022-23). Conversely, exclusion of people living with HIV increased (2012-13: not mentioned 64.3%; excluded 35.7%; 2022-23: not mentioned 21.4%; included with caveat 9.2%; excluded 69.4%). Disability was rarely explicitly addressed; however, consent-related and nonspecific exclusion criteria suggested potential indirect exclusion. Conclusion: Despite progress in select domains, areas such as HIV status, require further work to broaden criteria and better reflect the real-world populations. Our findings highlight the need for clearer and more equitable eligibility standards, thereby improving external validity and equity in cancer research.